PERAN PENDIDIKAN ISLAM DALAM PENGUATAN KARAKTER BANGSA DI ERA GLOBALISASI - Sulaiman, Sulaiman (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2025)
The background This study investigates the contribution of Islamic education in the formation and strengthening of the character of the Indonesian nation amidst the rapid flow of globalization. The phenomenon of globalization has brought about important transformations in various dimensions of life, including shifts in socio-cultural values that influence the formation of community identity. As an integral component of the national education system, Islamic education has a great capacity to instill fundamental values that are in line with the nation's identity. Using a qualitative methodology based on literature review and content analysis, the study identified three main aspects of the contribution of Islamic education in strengthening the nation's character: the application of spiritual-moral values in the learning process, the development of character education rooted in religious values and local wisdom, and the strengthening of the function of Islamic educational institutions in building national identity. The research findings indicate that the contribution of Islamic education, especially in the fields of tarbiyah, ta'lim and ta'dib has the potential to be an effective means of filtering the negative impacts of globalization while remaining open to positive developments in the modern world. The application of moderate Islamic values combined with local wisdom and national spirit has the potential to create a generation with strong character, clear identity, and a global outlook.